Peran Bahasa Dan Korelasinya Dengan Nilai-Nilai Pendidikan: (Studi Analitis atas Falsafah Taaj al-Ma’had di TMI Al-Amien Prenduan) - Cecep Sobar Rochmat; Yongki Sutoyo; Ardiyanti Ardiyanti; Abdurrahman Hilabi (Thawalib: Jurnal Kependidikan Islam, 2022)
TMI Al-Amien Prenduan is an educational institution that applies foreign languages (Arabic and English) as the language used in daily conversation. This study aims to find out how the role of language in TMI Al-Amien Prenduan and its correlation with the educational and analytical values of the Taaj al-Ma'had philosophy. The research method used is qualitative research with a literature study approach. Data collection techniques are sourced from book documentation, articles, etc. The data analysis technique uses an approach from Miles & Hubarman with 3 stages, namely data reduction, data presentation and data verification or conclusions. The data validity technique uses confirmability through a language development group (Markazul Lughoh) which holds various daily, monthly or yearly language activities. The results show that the role of language is quite closely correlated with educational values, because learning and using (foreign) languages will not run without education., because learning and using (foreign) languages will not run without education. Coupled with the Taaj al-Ma'had philosophy that is ingrained in TMI Al-Amien Prenduan, language will always live and develop throughout time. It can be concluded that the role of language in TMI Al-Amien Prenduan is a fairly important element because if the language is not alive, then the crown of the cottage (taaj al-Ma'had) will be damaged and not develop. Language development has the full support of Markazul Lughoh and all the functionaries of the boarding school, including the students who are active in foreign languages in daily conversation. The theoretical and practical implications can be stated, the theoretical implications, the application of listening, speaking, reading, writing, composing and translating skills will make it easier for students to learn the language, Markazul Lughoh has an important role in improving the language quality of students. Practical implications, the results of this study are used as input for students and all functionaries of the Al-Amien Prenduan Islamic boarding school to always use foreign languages in daily conversation accordance with the philosophy of language is Taaj al-Ma'had.